Beyond the liver: well-being as the bridge between fatigue and quality of life in chronic hepatitis B patients - Zheng, Caixia; Zhong, Chunxiu; Tang, Qingyun; Xie, Hongyan; Gao, Xinrui; Li, Bing; Yin, Junhua; Wei, Li (Frontiers in Public Health, 2025)
BackgroundChronic hepatitis B (CHB) remains a significant public health challenge. Many CHB patients experience fatigue and impaired mental health, affecting their health-related quality of life (HRQoL). This study investigates the relationships between fatigue, well-being, and HRQoL, while identifying risk factors for poor well-being in CHB patients.MethodsA cross-sectional study was conducted with 428 CHB patients. HRQoL, fatigue, and well-being were evaluated using the 36-Item Short Form Health Survey (SF-36), fatigue was measured using the Multidimensional Fatigue Inventory (MFI-20), and well-being was evaluated using the WHO-Five Well-Being Index (WHO-5). Logistic regression was conducted to evaluate the independent risk factor, and structural equation modeling was performed to explore the relationship between fatigue, well-being and HRQoL.ResultsA total of 315 CHB patients were classified as having high well-being, and 113 as having low well-being, based on WHO-5 scores. Patients in the low well-being group were more likely to be female (26.5% vs. 9.5%, p < 0.001), had lower body weight (60.88 ± 9.19 kg vs. 64.47 ± 10.96 kg, p = 0.002), and a higher prevalence of cirrhosis (35.4% vs. 21.6%, p = 0.004). Well-being scores were positively correlated with all eight HRQoL dimensions, and patients with higher well-being had significantly better HRQoL scores. Conversely, well-being was negatively correlated with fatigue levels, with higher fatigue scores linked to lower well-being. Structural equation modeling showed that fatigue significantly reduced well-being, which in turn decreased HRQoL. Multivariable analysis indicated that independent factors of poor well-being included female gender (OR = 2.692, p = 0.004), lower weight (OR = 0.971, p = 0.038), lower education level (OR = 0.642, p = 0.028), lack of physical exercise (OR = 0.541, p < 0.001), and cirrhosis (OR = 1.944, p = 0.017). For patients with cirrhosis, only female gender (OR = 5.884, p = 0.007) and lack of exercise (OR = 0.541, p = 0.023) were significant factors.ConclusionWell-being mediates the relationship between fatigue and HRQoL in CHB patients, underscoring its critical role in improving patient outcomes. Interventions targeting well-being, such as promoting physical activity, may enhance HRQoL and overall mental health in CHB patients.